Perancangan Interior Pusat Seni Rupa Murni di Surabaya - Tiffany Marissa Tandra; Yusita Kusumarini; Jean Francois Poilot (Intra, 2016)
Art is an aspect that cannot be separated from human life, but the state of the arts in the city of Surabaya is so undeveloped that public interest in the arts tend to be low, especially in visual art. Seeing the state of visual art in Surabaya that is not accommodated, and thus it needs a facility that can fulfill those needs which encompasses the functions of exhibition, education, recreation, and information.In this design process the problems are how to design the interior of visual art center that not only accommodate the needs of the arts in the city of Surabaya, but also attract visitors in accordance with the lifestyle of the metropolitan youth nowadays.The method used in this design follows the diagram Zeisel with additional adjustments of the drafting process, which explains the design process that rotates from the end result that can be returned to the initial stages of design to be fixed in order to achieve the most optimal results. Six of these methods include basic eb knowledge (preliminary stages of data collection), programming research (programming phase), design and design review (transformation stage design), construction (design development stage), use + adaptation (the final design stage), and evaluation research (evaluation phase).The final design is applied in the concept of 'recreational', and accommodate the needs of visual art in Surabaya by providing facilities such as spaces for education, information, exhibitions, and recreational which are exhibition area, library, lecture theater and studio, as well as supporting spaces such as cafes and offices. Meanwhile, in order to attract visitors in accordance with the lifestyle and culture of the people, the concept of 'recreation' is applied by creating new experiences and improving the quality of those experiences.